2023
DOI: 10.1021/acsestwater.2c00504
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Profiling of Pathogens in Simulated Reclaimed Water Distribution Systems Operated at Elevated Temperature Reveals Distinct Response of Mycobacteria to Filtration and Disinfection Conditions

Abstract: Distribution of reclaimed water presents distinct challenges for pathogen control relative to the distribution of conventional potable water. The elevated temperatures common in arid regions can exacerbate such challenges by accelerating disinfectant decay and increasing microbial growth rates. Here, we carried out a controlled, continuous-flow, head-to-head study of six simulated reclaimed water distribution systems (RWDSs) in order to assess whether treatments identified to be effective for microbiological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
(139 reference statements)
0
2
0
Order By: Relevance
“…phocaicum clade . Ghosh and colleagues reported that the operating conditions of simulated reclaimed water distribution systems can select for different NTM species . They found that chlorinated water was dominated by the rapidly growing Fortuitum-Vaccae clade, while chloraminated water contained a more diverse community, including the Abscessus-Chelonae , Terrae , and Fortuitum-Vaccae clades.…”
Section: Reflections and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…phocaicum clade . Ghosh and colleagues reported that the operating conditions of simulated reclaimed water distribution systems can select for different NTM species . They found that chlorinated water was dominated by the rapidly growing Fortuitum-Vaccae clade, while chloraminated water contained a more diverse community, including the Abscessus-Chelonae , Terrae , and Fortuitum-Vaccae clades.…”
Section: Reflections and Recommendationsmentioning
confidence: 99%
“…97 Ghosh and colleagues reported that the operating conditions of simulated reclaimed water distribution systems can select for different NTM species. 98 They found that chlorinated water was dominated by the rapidly growing Fortuitum-Vaccae clade, while chloraminated water contained a more diverse community, including the Abscessus-Chelonae, Terrae, and Fortuitum-Vaccae clades. Field and experimental research investigating the effects of geography, water sources (surface or groundwater), as well as plumbing conditions (such as water age, pipe material, temperature, and residual disinfectant levels) on NTM species diversity and composition will be crucial to elucidating the environmental transmission mechanisms of NTM.…”
Section: Species-level Characterization Of Ntm In Drinking Water: a C...mentioning
confidence: 99%